PARTISIPASI PUBLIK DALAM PENYELENGGARAAN TRANSPORTASI MASSAL KOTA SURAKARTA 2014-2015 - Priyatno Harsasto (Program Magister Ilmu Politik, Universitas Diponegoro, 2015)
Public participation is a requirement for governance to work in the name of a good public service delivery. Participation makes citizen’s voice and aspiration to be included and calculated in municipality’s policy. In this way, it requires the people to be active and in the same vein the government to be innovative. This research was conducted in this context. This research tried to elaborate the involvement of the citizen in public policies in Surakarta Municipality. The case in point was mass transportation policy in Surakarta Municipality, to find out how far the people aspiration have been included in the formation of public policy, and what was the stumbling blocs of this program. Using in-depth interview and documentation study, this research found that as mass transportation is a sectoral policy, it was still in the hand of technocrats, and in this way people participation was still marginal. However, in Surakarta mass transportation proggrams, could not be separated from the role of the people, through Musrenbang, public hearing, media as well as NGO’s advocacy for the government. In short, public participation has indeed owned their inclusion space, but they have to contend with elite biases. Technical and cultural blocks could be said to be the main reasons why public participation has still been weak in mass transportation program in Surakarta Municipality.Key words: mass transportation, public participation, elite-bias, technical and cultural blocks